Association between serum chloride and prevalence of metabolic syndrome in the general U.S. adult population: evidence from NHANES 2011–2018 - Lun Zhang; Hongpeng Liu; Xiaoling Lv; Jianmei Zhou; Rongfang Zhou; Wenming Xing; Qing Wu (BMC Endocrine Disorders)
Abstract Aim Numerous studies have revealed the decisive role of serum chloride in the outcome of specific patients. However, the potential role of serum chloride in general populations has been rarely investigated. This study aims to assess the association of serum chloride with MetS risk in the general population. Methods A total of 13,290 adult participants were obtained from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2018. The association between serum chloride and MetS was investigated using weighted logistic regression analyses. The weighted restricted cubic spline (RCS) was constructed based on the fully adjusted model to explore its dose-response relationship. Further stratified analyses were also conducted. All data and analyses were conducted using the “Survey” package in R software (Version 4.4.1). Results The average age of this population was 48.20 ± 0.35, the average BMI was 29.42 ± 0.12 kg/m2, included 48.54% males, and the weighted prevalence of MetS was 37.83%. After adjusting full covariates, serum chloride was negatively associated with MetS risk in overweight or obese participants who did not smoke or heavy drink. Meanwhile, serum chloride was significantly inversely correlated with the raised fast glucose (FG), total cholesterol (TG) and blood pressure (BP), and positively related with the reduced high density lipoprotein cholesterol (HDL-C). Consistent results were observed in the RCS analysis. Conclusion This study suggested a potential inverse relationship between serum chloride levels and MetS risk. Understanding this link may offer fresh perspectives on preventing and treating MetS, presenting new therapeutic targets and strategies for public health improvement.